2022
DOI: 10.1093/neuonc/noac242
|View full text |Cite
|
Sign up to set email alerts
|

A novel compound EPIC-0412 reverses temozolomide resistance via inhibiting DNA repair/MGMT in glioblastoma

Abstract: Background TMZ resistance has become an important obstacle affecting its therapeutic benefits. O6-methylguanine DNA methyltransferase (MGMT) is primarily responsible for the TMZ resistance in GBM patients. Additionally, active DNA damage repair pathways can also lead to TMZ resistance. Here, we reported a novel small-molecule inhibitor EPIC-0412 that improved the therapeutic efficacy of TMZ by inhibiting the DNA damage repair pathway and MGMT in GBM via epigenetic pathways. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Next, the study modeled the structure of the protein encoded by the gene locus with the high‐frequency mutation and found that the deletion of the amino acid at position 16 of ARID1A impairs its binding to the SWI/SNF complex's core subunit BRG1, leading to the abnormal function of the complex. Hence, by starting with the SWI/SNF complex's function and searching for its regulated transcription factors, certain findings substantiated that the E2F family proteins in gliomas play a pivotal role in DNA damage repair and sustaining cell survival, leading to TMZ (temozolomide) resistance 23 . Our results affirmed a correlation between its expression and ARID1A.…”
Section: Discussionsupporting
confidence: 67%
“…Next, the study modeled the structure of the protein encoded by the gene locus with the high‐frequency mutation and found that the deletion of the amino acid at position 16 of ARID1A impairs its binding to the SWI/SNF complex's core subunit BRG1, leading to the abnormal function of the complex. Hence, by starting with the SWI/SNF complex's function and searching for its regulated transcription factors, certain findings substantiated that the E2F family proteins in gliomas play a pivotal role in DNA damage repair and sustaining cell survival, leading to TMZ (temozolomide) resistance 23 . Our results affirmed a correlation between its expression and ARID1A.…”
Section: Discussionsupporting
confidence: 67%
“…The specialized regulation of DNA methylation damage repair pathway is the most useful application to improve TMZ treatment efficiency. Previously, some studies uncover that several mechanisms of MGMT inhibitors have been developed sensitizing cells to TMZ 16,17 . However, we are still unsatisfied with those inhibitors which are less effective, with more side effects and non‐specific targets.…”
Section: Discussionmentioning
confidence: 99%
“…As a well-known transcription factor, E2F1 regulates various DDR-related genes 47 . We previously reported that RAD51AP1 is a potential mediator of EGFRvIII and an oncogene in GBM 32 .…”
Section: Discussionmentioning
confidence: 99%